Bridging tourism, architecture, and sustainability: Design and development of an app for contemporary architecture built in Portugal - Martins, Nuno (2021)
Contemporary architecture has an increasing importance in tourism. The marketing implications of digital or mobile content in this niche tourism space has not been previously studied. With this project we aim to build a mobile app to cater to this market and show that it can positively impact tourism in Portugal. A two-step multidimensional approach was applied to achieve this goal. The first step was based on benchmarking, as well as interviews with two architects. The second step was based on visual identity factors, prototyping, and usability tests. We found that it was possible to develop an intuitive app that positively adjusted to the needs and preferences of future users. Improvements to the platform should include new metrics, blog links, and augmented reality.